Microshear bond strength of universal adhesives to enamel and dentin: an eighteen-month in vitro study - Garcia, Rubens Nazareno; Araújo Neto, Vitaliano Gomes de; Silva, Camila Ribeiro; Miguel, Luiz Carlos Machado; Giannini, Marcelo (Brazilian Dental Science, 2021)
Objective: The aim of this study was to evaluate the microshear bond strength of Universal adhesives to enamel anddentin after one week and eighteen months of water storage. Material and Methods: Fragments from the buccalsurfaces of 80 bovine teeth were prepared (12x5x1.0 mm) and ground to obtain flat surfaces of enamel and dentin.Samples were randomly assigned to 8 experimental groups (n=10), according to four adhesive systems (Adper SingleBond Plus/control – not a Universal adhesive/ASB; Ambar Universal/AUN; Prime&Bond Active/PBA and ScotchbondUniversal/SBU) and two water-storage times (one week and eighteen months after sample preparations). Adhesiveswere applied according to the manufacturers’ instructions and molds were positioned over bonded surfaces. A flowablecomposite was poured into the molds to fill up their internal diameter and obtain resin cylinder (1.0mm height/0.7mminternal diameter) after light-curing. Bond strength was determined using a testing machine (0.5 mm/min) and datawere statistically analyzed by two-way analysis of variance (ANOVA) and the post-hoc Tukey’s test (alpha=0.05).Failure patterns were analyzed for all resin cylinder tested. Results: For enamel, differences among adhesives wereobserved only at 18 months, in which SBU produced lower bond strength values (15.9±3.0 MPa) than the othersuniversal adhesives (AUN: 19.3±4.8 and PBA: 21.4±2.1 MPa) (p